Pengembangan wilayah Propinsi DIY (Pendekatan Teoritis) - Rudy Badrudin (Economic Journal of Emerging Markets, 1999)
The economic development process of Indonesia, in fact, has caused many distortions so that endanger the integration of nation. These distortions happened because of too centered development strategy causing distortion between central and region, and between region and region as well.